Effects of Methanolic Extract Based-Gel From Saudi Pomegranate Peels With Enhanced Healing Potential on Excision Wounds in Diabetic Rats - Karim, Shahid; Alkreathy, Huda M.; Ahmad, Aftab; Khan, Mohammad Imran (Frontiers in Pharmacology, 2021)
Introduction: The present study was designed to evaluate the wound healing activity of a Saudi pomegranate peel extract (SPPE) on excision wound healing in experimentally induced diabetes in rats. Methodology: Animals were divided into three groups after diabetic excision wound creation: no treatment, gel alone and Saudi pomegranate peel extract in gel. Animals were monitored for clinical signs, morbidity and mortality during entire study period. The efficacy parameters evaluated were percent wound contraction, Hydroxyproline content, estimation of TGF-ß1, VEGF, and EGF in wound lysates by ELISA, mRNA expression of TGF-ß1, VEGF, and EGF in wound lysates by qPCR, Estimation of nitric oxide (NO) and NO synthase (NOS) in Wound Lysates and histopathology of skin for reepithelization, neovascularization, and inflammation. Results: The Saudi pomegranate peel extract in gel (5.0 g extract per 100 g gel) showed significant wound healing activity when compared to the vehicle control [p<0.05] following twenty one days of treatment. Animals in the control and treatment groups were apparently normal through the study with no significant differences in body weights between groups. Expression of mRNA of TGFβ1, EGF and VEGF in wounds was the highest on day 14 post treatment 4.3, 3.5 and 0.9 fold higher respectively in the treatment group when compared to vehicle control, and on day 21, the values were 0.12, 0.3 and 0.83 respectively. No statistically significant differences were observed in TGF-ß1 levels in wounds on days 4, 7, 14 and 21 post treatment when compared to the vehicle control (p>0.05). Significantly higher levels of VEGF and EGF were observed in treatment group on day 7 and 21 when compared to vehicle control (p<0.05). Mean hydroxyproline levels and NOS activity were higher in treatment group on days 4 and 7 when compared to vehicle control. NO levels in treatment group were significantly lower on days 7, 14 and 21 when compared to vehicle control (p<0.05). Histopathological changes in skin wound in the treatment group were consistent with wound healing when compared to the vehicle group. Conclusion: This study’s findings suggest that SPPE gel may possess wound healing potential in experimentally induced diabetic conditions.